E-LOCATION KAFE DI KOTA PAYAKUMBUH - Anisya Anisya; Indra Warman; Dede Wira Trise Putra; Ganda Yoga Swara; Putri Mandarani (Ensiklopedia of Journal, 2023)
The web-based cafe e-location application in Payakumbuh is an application to display location points and detailed information about a cafe, where visitors who want to visit the cafe have no trouble finding the location of the cafe, and don't have to go far. directly to the cafe to find out prices, menus and other information related to the cafe. This system provides all the information needed by visitors who want to visit a cafe. This study aims to develop research results from previously published articles regarding problem analysis and data from the e-location cafe application into an application that is ready for use by users. In this study, the authors built an application using the native PHP programming language and MySQL database and OpenStreetMap as a GIS application.